2003
DOI: 10.1103/physrevb.68.233202
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for identification of the divacancy-oxygen center in Si

Abstract: A deep level transient spectroscopy ͑DLTS͒ study of electronic defect levels in 15 MeV electron irradiated n-type float-zone Si samples with different oxygen contents has been performed. Heat treatment at 250°C results in a shift of both the singly negative and doubly negative divacancy (V 2 ) related DLTS peaks. This is due to annealing of V 2 and the formation of a new double acceptor center. The formation of the new center has a close one-to-one correlation with the annealing of V 2 . The annealing rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
39
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 9 publications
5
39
0
2
Order By: Relevance
“…The V 2 O is the only one defect generated by a second order process that was evidenced by Electron Paramagnetic Resonance [53,54] as direct result of irradiation. On the other hand, there are studies based on the annealing of V 2 at high temperatures of diodes irradiated with small dose values that revealed the transformation of V 2 into another defect X in oxygen rich silicon [55,56]. In these publications the X-defect was associated also with the V 2 O-complex.…”
Section: Deep Acceptor I Pmentioning
confidence: 99%
“…The V 2 O is the only one defect generated by a second order process that was evidenced by Electron Paramagnetic Resonance [53,54] as direct result of irradiation. On the other hand, there are studies based on the annealing of V 2 at high temperatures of diodes irradiated with small dose values that revealed the transformation of V 2 into another defect X in oxygen rich silicon [55,56]. In these publications the X-defect was associated also with the V 2 O-complex.…”
Section: Deep Acceptor I Pmentioning
confidence: 99%
“…This is due to recent reports on the observation of a double acceptor center identified as the divacancy-oxygen center (V 2 O). [1][2][3] These reports have considerably improved the understanding of the mechanisms of V 2 annealing and, at the same time, raised new questions concerning the origin of the dominant mechanism.…”
mentioning
confidence: 96%
“…In particular, oxygen atoms were found to be effective traps for V 2 , and the divacancy-oxygen interaction was shown to be the main mechanism of the V 2 elimination upon annealing of irradiated Czochralski-grown (Cz) Si crystals. 4,9,10,[13][14][15][16][17] An EPR Si-A14 signal and an absorption line at 833.4 cm À1 have been assigned to a complex incorporating the divacancy and an oxygen atom (V 2 O). 14,16 Deep level transient spectroscopy (DLTS) studies on irradiated and annealed n-type Si crystals have shown that the V 2 O center possesses two acceptor levels at E c À 0.23 eV and E c À 0.47 eV.…”
mentioning
confidence: 99%
“…14,16 Deep level transient spectroscopy (DLTS) studies on irradiated and annealed n-type Si crystals have shown that the V 2 O center possesses two acceptor levels at E c À 0.23 eV and E c À 0.47 eV. 9,10,17 In p-type Si crystals a level at E v þ 0.24 eV, which appeared simultaneously with the disappearance of V 2 upon annealing, has been assigned to a donor level of the V 2 O complex. 15 We have argued in a recent work that in addition to the first donor level at E v þ 0.236 eV the V 2 O center possesses a second donor level at E v þ 0.087 eV.…”
mentioning
confidence: 99%